Entamoeba lysyl-tRNA synthetase contains a cytokine-like domain with chemokine activity towards human endothelial cells. - Manuel Castro de Moura; Francesc Miro; Jung Min Han; Sunghoon Kim; Antonio Celada; Lluís Ribas de Pouplana (Public Library of Science (PLoS), 2011)
Immunological pressure encountered by protozoan parasites drives the selection of strategies to modulate or avoid the immune responses of their hosts. Here we show that the parasite Entamoeba histolytica has evolved a chemokine that mimics the sequence, structure, and function of the human cytokine HsEMAPII (Homo sapiens endothelial monocyte activating polypeptide II). This Entamoeba EMAPII-like polypeptide (EELP) is translated as a domain attached to two different aminoacyl-tRNA synthetases (aaRS) that are overexpressed when parasites are exposed to inflammatory signals. EELP is dispensable for the tRNA aminoacylation activity of the enzymes that harbor it, and it is cleaved from them by Entamoeba proteases to generate a standalone cytokine. Isolated EELP acts as a chemoattractant for human cells, but its cell specificity is different from that of HsEMAPII. We show that cell specificity differences between HsEMAPII and EELP can be swapped by site directed mutagenesis of only two residues in the cytokines' signal sequence. Thus, Entamoeba has evolved a functional mimic of an aaRS-associated human cytokine with modified cell specificity.